FORMULATION AND ANTIOXIDANT ACTIVITY EMULGEL SENGGANI LEAF (Melastoma malabathricum L.) WATER FRACTIONS WITH VARIATIONS OF GELLING AGENT USING DPPH METHOD - Sultan, Andi Rizka Walyanda; Ropiqa, Meri; Apridamayanti, Pratiwi; Anastasia, Desy Siska (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
The senggani plant is reported to have antioxidant activity owing to its flavonoid content, which is a free radical scavenger. The water fraction of senggani leaves needs to be prepared for use, one of which is the emulgel. An important additional ingredient in emulgels is the gelling agent, and the most commonly used is carbopol 940. This study aimed to determine the formulation of emulgel preparations with the most stable variation in carbopol 940 and to test the antioxidant activity of water fraction emulgel preparations from senggani leaves (Melastoma malabatricum L.). The preparations were made by varying the concentrations of Carbopol 940 to 0.5% (F1), 1.25% (F2), and 2% (F3). Physical stability evaluations included organoleptic, homogeneity, pH, spreadability, adhesive power, viscosity, and antioxidant tests for 28 days. The results of the research showed that the emulgel that tested the physical stability of emulgel preparations with each concentration produced the best emulgel, F3 with an emulgel concentration of 2%, with a pH of 5.32-5.19, spreadability of 4.47-5.53 cm, adhesive power of 31. 21 -25.64 seconds, and viscosity of 47520-34853 cP. The IC50 value of the emulgel preparation is 17870.83-14851.28 ppm, with statistical test results of sig. (p-value) > 0.05, which means that storage has no effect on the emulgel preparation. The conclusion of this research is the best concentration of Carbopol as gelling agent of emulgel is 2% with the antioxidant activity is very weak Keywords: emulgel; senggani leaf water fraction; carbopol 940; IC50